Fatigue and fracture of adhesively-bonded composite joints : behaviour, simulation and modelling - Vassilopoulos, Anastasios P. (Woodhead Publishing, an imprint of Elsevier, 2015)
It is commonly accepted that the majority of engineering failures happen due to fatigue or fracture phenomena. Adhesive bonding is a prevailing joining technique, widely used for critical connections in composite structures. The demand for reliable and safe structures necessitates deep knowledge in this area in order to avoid catastrophic structural failures. This book reviews research in the field of fatigue and fracture of adhesively-bonded composite joints. Topics include: experimental investigation of the reliability of adhesively-bonded composite joints; current research on understanding damage mechanisms; fatigue and fracture; durability and ageing as well as implications for design; modelling of bond performance and failure mechanisms in different loading conditions. -- Edited summary from book.
Keywords: Materials -- Fatigue.; Fracture mechanics.; Adhesive joints.; elektronické knihy; electronic books